ANALISIS HUBUNGAN SELF EFFICACY TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA PADA MATERI LINGKARAN - Nurazizah, Sinta; Nurjaman, Adi (IKIP Siliwangi, 2018)
This study aims to analyze connection self-efficacy toward the ability of critical thinking on the material of circe of junior high school students. This research method using the qualitative descriptive method. This research is conducted in SMP Negeri 9 Cimahi in Grade IX of the academic year 2017-2018. The population of this study is the students of class IX SMP Negeri 9 and the subject of the research is all the students of class IX-A that consist of 34 students. To obtain the research data used the instrument in the form of test description and questionnaire self-efficacy. The results of the research concluded: (1) the level of students' mathematical critical thinking ability in the problem solution is still low; (2) students' difficulties, in general, have not understood the problem and the preconception is still low; (3) students have not embedded the sense of learning independently; (4)there are connection which is significant between self-efficacy toward mathematics critical thinking.